Stock Market Performance and Exchange Rate: Evidence from China - Kang, Rui-yang (2020)
The main trend of the Chinese economic developments could be summarized as the increasing international cooperation and trading competition in recent years, leading to much higher volatilities in both capital market and foreign exchange market, which caused increasing risks in terms of economic development and investments. And the Chinese government has proposed the goal of combing the internal and external circulations in the economy, trying to ensure the long-term steady work and growth of the domestic asset markets and to promote a healthier international cooperation and trading, which would improve the conditions of the stock market and the foreign exchange market and enable the them to have a better interaction. On this basis, it would be necessary and meaningful to empirically discuss the relation between the RMB exchange rate and the Chinese stock market performance in the New Normalcy time period. To this end, the daily closing price data of the “Wind World A Index” and the RMB to the USD exchange rate (mid-quoted price) from January 2016 to January 2020 are selected as variables in this dissertation to represent the Chinese stock market performance and the exchange rate respectively. And with the VAR model constructed, the Granger Causality test and the impulse response functions analysis based on the model, it could be concluded that there should exist the unidirectional and negative mean spill-over effect of the stock performance on the exchange rate, and the lagged values of the stock market performance could have the predictive ability over the RMB currency value. Generally, higher stock market performance tends to lead to higher RMB currency values in the future periods in the short term, which is conforming to the Stock-Oriented model. Then, the BEKK-GARCH model and the variance decomposition analysis also provided evidences of the unidirectional volatility spill-over effect from the stock market to the foreign exchange market. Finally, the empirical conclusions and remarks are summarized and stated together with several suggestions related to policy-making and investment.